2016
DOI: 10.1152/physiol.00048.2015
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Dysregulation of Adipose Tissue Autophagy in Obesity

Abstract: There is growing interest in understanding how dysregulated autophagy may contribute to pathogenesis of disease. Most frequently, disease states are associated with diminished autophagy, mostly attributed to genetic variation in autophagy genes and/or to dysfunctional posttranscriptional mechanisms. In human adipose tissue (AT), in obesity, expression of autophagy genes is upregulated and autophagy is likely activated, associating with adipose dysfunction. This review explores the emerging role of transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 75 publications
2
31
0
1
Order By: Relevance
“…4,5 In adipose tissue, how autophagy is dys-regulated remains unsettled, with a general agreement that autophagy genes are overexpressed in adipose tissue, particularly in depots and in obesity sub-types that are more associated with metabolic dysfunction. [6][7][8] Yet, although autophagy, particularly in chronic diseases, may be regulated also at the gene expression level, 9,10 much more is known about its more rapid regulation by post-translational modifications and proteinprotein interactions. Indeed, while two independent groups suggested that autophagic activity (i.e., 'flux') is inhibited in adipose tissue, 11,12 at least four groups, including our own, provided evidence that the elevated gene expression of autophagy genes in adipose tissue manifests by increased autophagic flux.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In adipose tissue, how autophagy is dys-regulated remains unsettled, with a general agreement that autophagy genes are overexpressed in adipose tissue, particularly in depots and in obesity sub-types that are more associated with metabolic dysfunction. [6][7][8] Yet, although autophagy, particularly in chronic diseases, may be regulated also at the gene expression level, 9,10 much more is known about its more rapid regulation by post-translational modifications and proteinprotein interactions. Indeed, while two independent groups suggested that autophagic activity (i.e., 'flux') is inhibited in adipose tissue, 11,12 at least four groups, including our own, provided evidence that the elevated gene expression of autophagy genes in adipose tissue manifests by increased autophagic flux.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies had shown that an increased transcription of autophagy-related genes and proteins is associated with a dysfunction of adipose tissues and a higher risk of the development of cardiometabolic diseases. (7,9) If this is the case, the LCD28 group, which demonstrated autophagic activities, had a higher risk for cardiometabolic diseases compared to the other groups and control.…”
Section: Discussionmentioning
confidence: 96%
“…(6) Adipocyte hypertrophy especially in visceral adipose tissues which found in obesity could induce autophagy. (7)(8)(9)(10) Autophagy is a lysosomal degradation pathway in which organelles and other components of the cell are compartmentalized within a doublemembran vesicle, the autophagosome, and undergoing degradation by lysosomal enzymes and recycled. It is essential for survival, differentiation, development, and cell homeostasis.…”
mentioning
confidence: 99%
“…To date, autophagy in ASCs represents a relevant topic. It significantly contributes to the dysregulation of the adipose tissue by controlling lipid accumulation, and balancing white and brown fat deposition (Singh et al, 2009;Maixner et al, 2016). Intriguingly, autophagy is enhanced in obesity and associated to visceral fat distribution (Kovsan et al, 2011), thus encouraging further investigations on the ability of the stromal subset during adipogenic commitment.…”
Section: Discussionmentioning
confidence: 99%